Lithium‐Sulfur Batteries: Nitrogen‐Doped Aligned Carbon Nanotube/Graphene Sandwiches: Facile Catalytic Growth on Bifunctional Natural Catalysts and Their Applications as Scaffolds for High‐Rate Lithium‐Sulfur Batteries (Adv. Mater. 35/2014). (September 2014) - Tang, Cheng; Zhang, Qiang; Zhao, Meng‐Qiang; Huang, Jia‐Qi; Cheng, Xin‐Bing; Tian, Gui‐Li; Peng, Hong‐Jie; Wei, Fei
<x xml:space="preserve">Abstract</x> Nitrogen‐doped aligned carbon nanotube/graphene sandwiches are rationally designed and fabricated in situ on bifunctional natural catalysts by Q. Zhang, F. Wie, and co‐workers on page 6100. The sandwiches exhibit high‐rate performances as scaffolds for lithium–sulfur batteries. Such a design strategy opens the door to interface‐modified hierarchical nanocarbons for broad applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>